Spiritual di Tengah Scrolling: Tindakan Sosial Weber dan Fenomena Dakwah Digital Hanan Attaki - Rizki Rahmadani; Safa Anzila Madaniah; Qori Srirahmawati; Nida Khairina; Desi Erawati (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
The development of digital technology has fundamentally changed the landscape of religious communication, including the practice of Islamic da'wah in Indonesia. In the midst of social acceleration characterized by the explosion of information and the existential exhaustion of the younger generation, digital da'wah exists not only as a transfer of medium, but as an ecosystem of religious communication with its own social dynamics. This study aims to analyze the structure of the muhasabah message in Hanan Attaki's da'wah content with the theme Pause, Ramadan Reset, and Spiritual Detox, as well as interpret how the message moves various typologies of social action within the theoretical framework of Max Weber. The study used a qualitative approach with an interpretive content analysis design on video content on @hanan_attaki Instagram accounts during the Ramadan 1446 H period, selected through purposive sampling techniques. The analysis is carried out in three layers: structural descriptive, Weberian interpretive, and contextual critical synthesis. The findings show that the muhasabah message in the content works through a layered mechanism of meaning that simultaneously drives affective, value rational, instrumental rational, and traditional actions. The charismatic authority of the preacher acts as an amplifier that amplifies the resonance of the message, and this mechanism is modified by the digital platform infrastructure. This research implies that the effectiveness of digital da'wah is not solely determined by popularity, but by the ability of messages to activate the structure of meaning that has been embedded in the audience.